STRATEGI PENYAJIAN PROGRAM PENDIDIKAN MATEMATIKA UNTUK SEKOLAH DASAR DI TELEVISI EDUKASI (PRA PRODUKSI, PRODUKSI, PASCA PRODUKSI, PENAYANGAN) (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractPresentation impressions in Mathematics Education program is not as easy serving educational television programs other subjects such as subjects Language,Social Sciences. Right strategy required primarily to determine the appropriate format, so that math program that aired besides imparting education messages can also attract the target audience of students that love math. The author conducted research into how television Educational Kemendikbud do math program strategies to be favored by the target audience as expected. Research conducted by the author is a single case study analysis unit multi-unit analysis. The author conducted in-depth engineering inerview or in-depth interviews with Executive Producer Education program as Key Informant, producers and directors Mathematics Education program as an informant. The conclusion that the authors obtained, most of the stages of production of math education programs for elementary school has done well, but there are problems in determining the duration of which is not appropriate. Keywords : Strategy , Program of Education , Mathematics AbstrakPenyajian tayangan program pendidikan Matematika tidak semudah menyajikan program televisi pendidikan mata pelajaran lainnya seperti Mata pelajaran Bahasa, Ilmu Pengetahuan Sosial. Diperlukan strategi yang tepat terutama untuk menentukan format yang sesuai,agar program matematika yang ditayangkan selain menyampaikan pesan pendidikan juga bisa menarik minat siswa target audiens agar menyukai mata pelajaran matematika. Penulis melakukan penelitian bagaimana televisi Edukasi Kemendikbud melakukan strategi agar program matematika bisa disukai oleh target audiens sesuai dengan yang diharapkan. Penelitian yang dilakukan penulis adalah penelitian studi kasus tunggal dengan unit analisis multi unit analisis. Penulis melakukan teknik in-depth inerview atau wawancara mendalam dengan Executive Producer program Pendidikan sebagai Key Informan, Produser dan pengarah acara program Pendidikan Matematika sebagai Informan. Kesimpulan yang penulis peroleh, sebagian besar tahapan produksi program pendidikan matematika untuk sekolah dasar telah dilakukan dengan baik tetapi ada masalah dalam penentuan durasi yang tidak sesuai. Kata Kunci : Strategi, Program Pendidikan, Matematika